Nutrient Cycling in Grazed Pastures - Maria L. Silveira; Joao M. Vendramini; Hiran M. da Silva; Mariana Azenha (EDIS)
Many forage-based livestock production systems in Florida are characterized by extensive grazing with minimal inputs of commercial fertilizer and supplemental feed. In these systems, adequate soil fertility conditions are essential to sustain forage production. If nutrients become deficient, pasture and animal performance is reduced, and the economic returns of livestock operations may decline. This 3-page fact sheet discusses the different nutrient pathways in grazing pastures to help producers better understand how to promote nutrient cycling and pasture sustainability. Written by Maria L. Silveira, Joao M. B. Vendramini, Hiran M. da Silva, and Mariana Azenha, and published by the UF Department of Soil and Water Science, January 2013.